Advances in Operation, Optimization, and Control of Smart Grids - Murilo E. C. Bento; Hugo Morais (Electricity)
Power systems are equipped with a set of equipment for the generation, transmission, and distribution of electrical energy to consumption centers in a continuous manner and with quality indices [...]